American Dreams and Black Identity in the New African Diaspora: Chimamanda Ngozie Adichie’s Americanah and Yaa Gyasi’s Homegoing - Patrizi, Chiara (Oltreoceano - Rivista sulle migrazioni, 2022)
This essay examines how the New African Diaspora challenges and expands the notion of Black identity through the heritage, histories, and the African immigrants dreams of America and through which they measure and deal with reality. Thus, in the works of C.N. Adichie and Y. Gyasi, blackness is a fluid, collective identity, able to cross time and space renewing itself each time. Sogni americani e identità nera nella nuova diaspora africana: Americanah di Chimamanda Ngozie Adichie e Homegoing di Yaa Gyasi Il saggio esamina i modi in cui la nuova diaspora africana mette alla prova ed espande il concetto di identità nera attraverso l’eredità culturale, le storie e i sogni dell’America degli immigrati Africani e attraverso i quali misurano e affrontano la realtà. Così, nei romanzi di C.N. Adichie e Y. Gyasi, l’identità nera è fluida e collettiva, capace di attraversare spazio e tempo rinnovandosi ogni volta.